A ANTA DO MONTE VELHO (MONFORTE, PORTUGAL) - Rocha, Leonor (2015)
The dolmen Monte Velho 1 (Monforte, Portugal) is integrated in megalithic tour guide created by the municipality Monforte, and is the first in a séries of four monuments (one menhir and three dolmens) to be excavated under the project " Archaeological Map of Monforte ", the scientific responsibility of the signatory . The work done in the last two years (2011 and 2012) were aimed at excavation of the monument and evaluating the extent of damage caused by violations and acts of vandalism perpetrated in unknown date. The monument had a completely damaged chamber having its archaeological level completely removed. This could also be noticed in part of the corridor (near the camera) where prehistoric materials appeared mixed with other more recent chronology. Compared to the architecture, we can see that it was a monument with a singularity since the runner, unlike the applicant in other monuments in the region presents a misaligned with the axis of the runner chamber